Use of Reproductive Health Information among University Undergraduates in Ogun State, Nigeria - Adeyoyin, Samuel Olu (International Journal of Knowledge Content Development & Technology, 2017)
Abstract Young adults bear a higher risk of reproductive health problems than adults. Cases of unwanted pregnancies and their attendant complications reportedly rank among the highest in Africa. This study therefore investigates reproductive health and use of health information among university undergraduates in Nigeria. Correlational research design was adopted using descriptive survey method. Questionnaire was designed and used as survey instrument. The study used 25% of 6,978 undergraduate students from government and private universities in Abeokuta, Ogun State between 16-24 years old from each of the 35 departments that made up 8 colleges in the two universities. A total number of 1,745 copies of questionnaire were administered to the respondents out of which 1,500 copies were filled completely and retrieved making the response rate to be 86.95%. The findings of this study show that friends, parents and relatives were the closest sources of health information the respondents have used for reproductive health purposes. Utilisation of health information through information resources was effective. The study also concludes that cultural value, level of education and unfriendly attitude of health officials were parts of the major problems confronting effective utilization of reproductive health information among young adults in Nigeria. URL: http://ijkcdt.net/xml/11662/11662.pdf